The Superficial Stromal Scar Formation Mechanism in Keratoconus: A Study Using Laser Scanning In Vivo Confocal Microscopy. (18th January 2016) - Song, Peng; Wang, Shuting; Zhang, Peicheng; Sui, Wenjie; Zhang, Yangyang; Liu, Ting; Gao, Hua
Abstract : To investigate the mechanism of superficial stromal scarring in advanced keratoconus using confocal microscopy, the keratocyte density, distribution, micromorphology of corneal stroma, and SNP in three groups were observed. Eight corneal buttons of advanced keratoconus were examined by immunohistochemistry. The keratocyte densities in the sub-Bowman's stroma, anterior stroma, and posterior stroma and the mean SNP density were significantly different among the three groups. In the mild-to-moderate keratoconus group, activated keratocyte nuclei and comparatively highly reflective ECM were seen in the sub-Bowman's stroma, while fibrotic structures with comparatively high reflection were visible in the anterior stroma in advanced keratoconus. The alternating dark and light bands in the anterior stroma of the mild-to-moderate keratoconus group showed great variability in width and direction. The wide bands were localized mostly in the posterior stroma that corresponded to the Vogt striae in keratoconus and involved the anterior stroma only in advanced keratoconus. Histopathologically, high immunogenicity of α -SMA, vimentin, and FAP was expressed in the region of superficial stromal scarring. In vivo confocal microscopy revealed microstructural changes in the keratoconic cone. The activation of superficial keratocytes and abnormal remodeling of ECM may both play a key role in the superficial stromal scar formation in advanced keratoconus.